ANALYSIS OF INHERITANCE DISTRIBUTION FOR CHILDREN FROM A SECOND WIFE ACCORDING TO INHERITANCE LAW IN INDONESIA - Nurul Febriyanti; Syahrul Syahrul; Surono Zr (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
In Indonesia, dividing an inheritance can become particularly challenging when it involves a second wife and children from different marriages. One of the most sensitive issues is determining each child's rightful share, especially when the legal status of the second marriage is uncertain. This study uses a qualitative library research method, drawing from both primary legal texts and supporting literature to explore this issue.The findings, based on the study “Analysis of Inheritance Distribution for Children of a Second Wife According to Indonesian Inheritance Law”, show that Islamic inheritance law in Indonesia generally aims to provide a fair and balanced distribution through the principles of faraidh. As long as the second marriage is legally recognized, children from that union have the same inheritance rights as those from the first marriage. In practice, however, problems often occur when the second marriage hasn't been officially registered. This highlights the importance of legally documenting all marriages to protect the rights of every child and avoid future disputes among heirs.